Early reduction of matrix metalloproteinase-8 serum levels is associated with leptin drop and predicts diabetes remission after bariatric surgery. (15th October 2017) - Liberale, Luca; Bonaventura, Aldo; Carbone, Federico; Bertolotto, Maria; Contini, Paola; Scopinaro, Nicola; Camerini, Giovanni Bruno; Papadia, Francesco Saverio; Cordera, Renzo; Camici, Giovanni Guido; Dallegri, Franco; Adami, Gian Franco; et al.
Abstract: Background: We aimed at investigating whether the acute abrogation of leptin after bariatric surgery is able to reduce neutrophil activation and potentially affect type 2 diabetes mellitus (T2DM) remission. Methods: Metabolic and inflammatory parameters ( i.e. leptin, IL-6 and neutrophil products) were compared at baseline (before bariatric surgery), one month, one and three years after surgery in morbid obese (MOB) T2DM patients ( n = 12) and non-MOB controls ( n = 32). In vitro, the effects of leptin on Il-6-induced human neutrophil degranulation and integrin upregulation were assessed. Results: At baseline, MOB T2DM patients had a similar demographic, lipid and glycemic profiles than non-MOB T2DM controls, but higher levels of inflammatory mediators, such as CRP, fibrinogen, neutrophil-to-lymphocyte ratio (NLR), matrix metalloproteinase (MMP)-8 and leptin. One month after surgery, CRP, fibrinogen and MMP-8 were reduced only in MOB T2DM patients, while serum leptin was reduced in both groups. In the overall cohort, leptin and MMP-8 drops from baseline to one month post-surgery were positively correlated (Δleptin vs. ΔMMP8: r = 0.391, p = 0.025). Moreover, ΔMMP8 inversely correlated with fasting glucose levels at one-year follow-up and with glycated hemoglobin at both one- and three-year. At the cut-off point identified by ROC curve analysis (> 0 ng/mL), ΔMMP8 predicted complete T2DM remission at 3-year follow-up. In vitro, leptin increased IL-6-induced MMP-8 release and abrogated CD18 up-regulation. Conclusion: Bariatric surgery is associated to an acute abrogation of leptin that could affect MMP-8 levels, particularly in MOB T2DM patients. This beneficial event is associated with T2DM remission at 3-year follow-up. Highlights: MOB T2DM patients showed higher inflammation than non-MOB T2DM controls. The post-surgery drops of MMP8 and leptin can predict 3-year complete T2DM remission. In vitro, leptin directly activates IL-6-induced neutrophil degranulation.